Analysis of the biodegradative and adaptive potential of the novel polychlorinated biphenyl degrader Rhodococcus sp. WAY2 revealed by its complete genome sequence - Garrido-Sanz, Daniel; Sansegundo-Lobato, Paula; Redondo-Nieto, Miguel; Suman, Jachym; Cajthaml, Tomas; Blanco-Romero, Esther; Martin, Marta; Uhlik, Ondrej; Rivilla, Rafael (Microbial genomics, 2020)
The complete genome sequence of Rhodococcus sp. WAY2 (WAY2) consists of a circular chromosome, three linear replicons and a small circular plasmid. The linear replicons contain typical actinobacterial invertron-type telomeres with the central CGTXCGC motif. Comparative phylogenetic analysis of the 16S rRNA gene along with phylogenomic analysis based on the genome-to-genome blast distance phylogeny (GBDP) algorithm and digital DNA-DNA hybridization (dDDH) with other Rhodococcus type strains resulted in a clear differentiation of WAY2, which is likely a new species. The genome of WAY2 contains five distinct clusters of bph, etb and nah genes, putatively involved in the degradation of several aromatic compounds. These clusters are distributed throughout the linear plasmids. The high sequence homology of the ring-hydroxylating subunits of these systems with other known enzymes has allowed us to model the range of aromatic substrates they could degrade. Further functional characterization revealed that WAY2 was able to grow with biphenyl, naphthalene and xylene as sole carbon and energy sources, and could oxidize multiple aromatic compounds, including ethylbenzene, phenanthrene, dibenzofuran and toluene. In addition, WAY2 was able to co-metabolize 23 polychlorinated biphenyl congeners, consistent with the five different ring-hydroxylating systems encoded by its genome. WAY2 could also use n-alkanes of various chain-lengths as a sole carbon source, probably due to the presence of alkB and ladA gene copies, which are only found in its chromosome. These results show that WAY2 has a potential to be used for the biodegradation of multiple organic compounds.
Keywords: alkylační opravný homolog; biodegradace; Polychlorinated Biphenyls; PAH; complete genome; Whole Genome Sequencing; High-Throughput Nucleotide Sequencing; polychlorované bifenyly; RNA, Ribosomal, 16S; shluková analýza; hydrocarbons; biodegradation; Phylogeny; Naphthalenes; PCB; xyleny; AlkB Enzymes; sekvenování celého genomu; vysoce účinné nukleotidové sekvenování; Xylenes; naftaleny; Biodegradation, Environmental; Rhodococcus; Cluster Analysis; fylogeneze; RNA ribozomální 16S